APLIKASI SISTEM INFORMASI GEOGRAFIS (SIG) UNTUK ANALISIS AKSES TERDEKAT DAN JUMLAH PERGERAKAN PENDUDUK MELEWATI JALUR EVAKUASI DI KOTA PADANG - Rezki, Afrital (Program Studi Pendidikan Geografi STKIP PGRI Sumatera Barat, 2015)
Research on the location and evacuation pathways important as an effort to mitigate the earthquake and tsunami. The geological, geomorphological and climatological, several areas in the city of Padang is indicated as a disaster-prone areas that need to be done a variety of disaster mitigation efforts. The purpose of this study was to analyze (1) the evacuation route and the service sector that any evacuation routes, and (2) an analysis of the movement of residents in the evacuation path. The method used is the analysis of GIS with spatial-based descriptive research method to describe the area of research with qualitative data and this kuantitatif.Saat in Padang there are 10 evacuation route sectors which are directly related to the safe zone. The road is used as an evacuation route and have a sufficient width is Jln. Adinegoro with a width of 16 m. Which is the main road evacuation but did not have sufficient width is Jln. Black stumps with a width of only 3 m. The amount of movement of the population most at-prone zones leading to safe zones exist in the sector towards sector 7 as many as 51 175 lives in the district. East Padang.Keywords: SIG, Line Evacuation, population movements, Kota Padang